2017
DOI: 10.1063/1.4979900
|View full text |Cite
|
Sign up to set email alerts
|

Tunable organic PV parallel tandem with ionic gating

Abstract: A novel type of tunable organic photovoltaic (OPV) tandem device with ionic gating by in-situ ionic liquid is presented. This device is comprised of two solution-processed polymeric OPV cells connected in parallel by a dry-laminated transparent multiwall carbon nanotube (MWCNT) interlayer. The interlayer MWCNT of this 3-terminal tandem device plays a role of a common electrode with a Fermi level that can be tuned via ionic gating to turn it into a common cathode, collecting photo-generated electrons from both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…It was considered that both the type and size of the anion play critical roles in the polarizability and adsorption of the ions at the materials interfaces. The experimental studies demonstrated the order of carrier injection efficiency for the widely used ILs: BMIM-OTf > DEME-TFSI > BMIM-TFSI > DEME-BF4 > BMIM-BF4 > BMIM-PF6. , We have chosen DEME-BF4 as an exemplary IL in our current studies since it has one of the largest voltage stability window and since it was used in our earlier studies of gating in BHJ OPV. ,, On the other hand, different ILs have been tested as well, such as BMIM-BF4 and BMIM-PF6 for ionically gated hybrid PVs, and a separate paper is in preparation. While results on IL effects for the case of BMIM are indeed different from that of DEME-BF4, they are beyond the scope of this paper, but some differences are shortly described in the Supporting Information (Section S6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was considered that both the type and size of the anion play critical roles in the polarizability and adsorption of the ions at the materials interfaces. The experimental studies demonstrated the order of carrier injection efficiency for the widely used ILs: BMIM-OTf > DEME-TFSI > BMIM-TFSI > DEME-BF4 > BMIM-BF4 > BMIM-PF6. , We have chosen DEME-BF4 as an exemplary IL in our current studies since it has one of the largest voltage stability window and since it was used in our earlier studies of gating in BHJ OPV. ,, On the other hand, different ILs have been tested as well, such as BMIM-BF4 and BMIM-PF6 for ionically gated hybrid PVs, and a separate paper is in preparation. While results on IL effects for the case of BMIM are indeed different from that of DEME-BF4, they are beyond the scope of this paper, but some differences are shortly described in the Supporting Information (Section S6).…”
Section: Methodsmentioning
confidence: 99%
“…So, the initial motivation of our present paper is to create a small-molecule OPV device in which n-doping can be easily achieved in a system of porous CNT electrodes coated on top of the fullerene film ETL of a most simple two-layer OPV: CuPc/fullerene with the methods of reversible ionic EDLC. This requires a new architecture which combines an IL supercapacitor, connected in parallel with OPV as we introduced earlier for a polymeric OPV with IL and demonstrated its advantages in tandems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at higher Vbias of 2V, the internal E-field in PCBM most probably pulls MA + ions further into the PCBM layer. Also this is a hypothesis at this stage (not yet confirmed by direct measurement of ions present in ETL) for explaining EL improvement dynamics, we believe that this ETL doping is highly preferable by porous structure of fulleride (C60 and PCBM) molecular solids This type of penetration of ions into PCBM [23] and into C60 ETLs was demonstrated in [23][24][25][26][27][28] by external ionic gating in ionic liquids. The MA+ ions coming from PS have smaller size as compared to large ions of ionic liquids, and they can easily penetrate into PCBM, once there is a driving force for this.…”
Section: Resultsmentioning
confidence: 91%
“…This requires new architecture, which combines IL supercapacitor, connected in parallel with OPV as we introduced earlier for a polymeric OPV with IL, 25 and demonstrated its advantages in tandems. 27 In this paper, we apply the gating in IL to classical small molecule OPV with DEME−BF 4 IL and study the dynamics of this ionically gated system of MWCNT@Fullerene (i.e. cathode@ETL) to understand how it accumulates electrons, and how the ions move first in MWCNT network and then into and through fullerene molecular ETL layer of different thicknesses.…”
Section: Introductionmentioning
confidence: 99%